BRINGING THEORY TO LIFE: COLLABORATIVE DISCOURSE MARKER ACTIVITIES IN ELT (ENGLISH LANGUAGE TEACHING) CLASSROOMS (Educator Insights: Journal of Teaching Theory and Practice, 2026)
In this article, the possibility of teaching discourse analysis practically rather than relying only on theoretical lessons is analytically presented using the theme of discourse markers as an example. It emphasizes the improvement of lesson quality and student engagement through the use of various classroom activities